Prevalence, patterns, drivers, and perceived benefits of herbal medicine use in COVID-19 patients in Qatar - Raneem Alsheikh; Fatima R. Alsharif; Nouran Alwisi; Zachariah Nazar; Mohamed Ahmed Syed; Hamda Abdulla Qotba; Layla Al-Mansoori; Zumin Shi; Abdullah A. Shaito (Journal of Pharmaceutical Policy and Practice, 2025)
Background Coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), emerged as a global health crisis in early 2020, leading to widespread morbidity and mortality. In Qatar, as of December 2024, the disease burden has reached over 500,000 cases and more than 600 deaths. While conventional treatments have evolved throughout the pandemic, the use of Complementary and Alternative Medicine (CAM), particularly herbal medicine, has also become prevalent. This study investigated the prevalence, reasons, uses, types, self-reported benefits, and sociodemographic determinants of utilising herbal medicine among COVID-19 patients in Qatar.Methods A cross-sectional study was conducted among patients attending Qatar Primary Health Care Corporation (PHCC) clinics. Of the 10,000 SMS invitations that were sent, 882 survey responses were received from patients diagnosed with COVID-19 between 1 March 2020, and 30th April 2022. Following the exclusion of 31 participants due to missing data, sociodemographic data from 851 participants were analysed using logistic regression to assess predictors of herbal medicine use. Prevalence, patterns, types, and self-reported benefits were analysed using descriptive statistics.Results Of the 851 respondents included in the analysis, 440 (51.7%) reported herbal medicine use. Herbal medicine use was associated with better-perceived health outcomes. Women were more likely to use herbal medicine than men (OR = 1.90, 95%CI: 1.30–2.77, p = 0.001). The most used herbal remedies were ginger (n = 347), turmeric (n = 207), and garlic (n = 155). Family tradition (42%), the belief that herbs are natural (34.8%), and the desire to improve health and survival (31.1%) were the leading drivers of herbal medicine use.Conclusion Herbal medicine use was prevalent (51.7%) during COVID-19 in Qatar, with a higher prevalence of use among women. This prevalence was driven by cultural beliefs and perceived health benefits. The study contributes insights to guide future research, policy, and practice toward safe and evidence-informed integration of herbal medicine in pandemic preparedness and broader healthcare strategies.